Efek Hepatoprotektif Ekstrak Ethanol Buah Strawberry (Fragaria Sp.) Pada Kerusakan Oksidatif Hepar Mencit (Mus Musculus) Yang Diinduksi Parasetamol Dengan Indikator Kadar SGPT - Nurrochmah, Laela; , Dr. Devi Usdiana Rosyidah, M. Sc (2017)
Fragaria Sp. contains flavonols, ellagic acid, antosianin, vitamine A, B and C which have hepatoprotective effect. The aim of this study is to determine the hepatoprotective effect of strawberry (Fragaria Sp.) were evaluated from the decreases value of SGPT in mice with paracetamol induced. This study was a laboratorium experimental study with posttest only control group design. The objects of study were 30 male mice, weight 20-30 grams, aged 13 months, and divided into 6 groups by incidental sampling, the groups were positive control (paracetamol 5,07ml/gBW), negative control (Aquadest 1 ml), extract ethanol strawberry (Fragaria Sp.) dose I (0,5mg/20gBW), extract ethanol strawberry (Fragaria Sp.) dose II (1,0mg/20gBW), and extract ethanol strawberry (Fragaria Sp.) dose III (2,0mg/20gBW). After applying treatment and damaged hepar induced by paracetamol, decrease value of SGPT in mice were observed and calculated where the value of SGPT came from mice blood taken from retro-orbita. Data were analyzed with statistical test Kruskal-Wallis and followed by post hoc test Mann-Whitney. Ethanol extract of strawberry (Fragaria Sp.) dose I (0,5ml/20gBW), dose II (1,0ml/20gBW) dan dose III (2,0ml/20gBW) have the hepatoprotective effect by decreasing value of SGPT with paracetamol induced, with the mean number of SGPT are 78,42; 46,94 and 22,95 respectively. Based on the results of Kruskal-Wallis statistical test, p value = 0.000 (p <0.005) showed significantly different mean of the number of value SGPT in the sixth group after being treated. Ethanol extract of strawberry (Fragaria Sp.) dose I (0,5ml/20gBW), dose II (1,0ml/20gBW) dan dose III (2,0ml/20gBW) have the hepatoprotective effect by decreasing value of SGPT with paracetamol induced. Keywords : Fragaria Sp., hepatoprotective, paracetamol, mice